(3UaI GdUahIs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s; (3CHj fYje CMeO Hf YHO Gddg Hf egQGf GdCUHgGfj,J (B430 (3g` s ((3HQcGJ Hf KGHJ Hf MeO s)
(3ChdgG (B:s
(3GdLfjO Hf eMeO Hf GdLfjOCHhGdbGSe s
(3BNQgG (B:s
(3hbGdJ ZRGdI(B: (3GTJZd HChdi GdCehQ Hc , hdGJZad Yf SGYI Ef aGJc de JOQcgG hGdMeO ddg HBNQ cJGH UaI GdUahI s
(3GdLRA GdKGfj ef fSNI KGdKIs
(3HBNQgG JeRjbs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJGQjNs